APPLICATION OF PHOTOGRAMMETRY AND LASER SCANNING IN PROTECTING THE CULTURAL AND HISTORICAL HERITAGE - Admir Mulahusić; Nedim Tuno; Jusuf Topoljak; Džemaila Balić; Edin Hadžiosmanović; Sonja Stanić; Amir Hajdar (Geodetski Glasnik, 2013)
During the period of one hundred years photogrammetry has had and still has a very important role in the documentation of cultural heritage. Selecting proper technologies enabled the protection, preservation and valorisation of architectural, archaeological and other forms of cultural heritage. Many recent technological breakthroughs have improved photogrammetry, as a tool for capturing, allowing a representation of much more complicated objects. In this way the faithful representation of the real world as a fast flow of information from the experts to the user has been secured. This paper explains the importance of preserving and documenting the cultural and historical heritage. Interesting examples of documenting the cultural and historical heritage of the world and Bosnia and Herzegovina are given, using close-range photogrammetry and laser scanning.